Mining, Poverty, and Income Inequality in Central and Eastern European Countries: What Do the Data Tell Us? - Kunofiwa Tsaurai (Comparative Economic Research. Central and Eastern Europe, 2021)
The study investigates the effect of mining on both poverty and income inequality in Central and Eastern European countries (CEECs) using econometric estimation methods with panel data spanning from 2009 to 2019. Another objective of this paper was to determine if the complementarity between mining and infrastructural development reduced poverty and or income inequality in CEECs. What triggered the study is the failure of the existing literature to have a common ground regarding the impact of mining on poverty and or income inequality. The existing literature on the subject matter is contradictory, mixed, and divergent; hence, it paves the way for further empirical tests. The study confirmed that the vicious cycle of poverty is relevant in CEECs. According to the dynamic generalized methods of moments (GMM), mining had a significant poverty reduction influence in CEECs. The dynamic GMM and random effects revealed that the complementarity between mining and infrastructural development also enhanced poverty reduction in CEECs. Random effects and pooled OLS shows that mining significantly reduced income inequality in CEECs. However, random effects and the dynamic GMM results indicate that income inequality was significantly reduced by the complementarity between mining and infrastructural development. The authorities in CEECs are therefore urged to implement mining growth and infrastructural development-oriented policies in order to successfully fight off the twin challenges of poverty and income inequality.
Keywords: I3; I14; I24; L71; N14; 330; mining; poverty; income inequality; panel data; CEECs